Gambaran Prokrastinasi Penyelesaian Skripsi pada Mahasiswa yang Tidak Lulus Tepat Waktu - Cindy Octavia Tanjaya; Debora Basaria (Syntax Corporation Indonesia, 2024)
This research aims to analyze procrastination behavior among University X students class 2018-2020 who have not completed their thesis on time. The research approach used was qualitative with a phenomological method, involving five participants who met the research criteria. Data was obtained through partially structured in-depth interviews, then analyzed using narrative methods. The research results identified that internal factors, such as low motivation, lack of self-regulation abilities, and non-optimal thinking strategies, are the main triggers for procrastination. External factors, including parenting styles, limited social support, and a less conducive academic environment, also influence these delays. The impacts of this behavior include increased levels of stress, anxiety, decreased quality of learning, and delays in graduation which can affect students' futures. It is hoped that these findings can become a reference for educational institutions to develop programs or policies that help students complete their theses on time. This research also provides insight for students regarding the importance of motivation and time management in completing academic assignments.